Consolidation of the new nuclear calculation methodology of the IEA-R1 reactor - Stefani, Giovanni Laranjo; Conti, Thadeu das Neves (Revista Internacional de Ciências, 2018)
The IEA-R1 neutron and thermo-hydraulic calculation methodology is composed of 5 computational codes from the area of ​​reactor physics, which have a symbiotic dependence on each other. Since the outputs of each code will be used to generate the input of the next code. The programs involved in this methodology are LEOPARD, HAMMER-TECHNION, TWODB, CITATION and COBRA. Each of these codes is responsible for a specific type of calculation. In a first two-year study, between the years 2008 and 2010, these IEA-R1 nuclear reactor codes were integrated into a single management code. This management code had as main objective the reduction of the time spent by the calculation team of the reactor and to prevent against errors in the manipulation of data and data output. In this study the calculation time was reduced by 99%. The present article presents the closing of this work, being a document with the consolidation of 7 years of the use of the new calculation methodology implemented in the IEA-R1 reactor, demonstrating its efficiency and reliability, besides the proper registration of this project that had great importance Within the IPEN research reactor.